KEWAJIBAN YURIDIS MENYESUAIKAN ANGGARAN DASAR YAYASAN YANG MENJALANKAN KEGIATAN PENDIDIKAN BERDASARKAN PP NOMOR 2 TAHUN 2013 - MUHAMMAD JELI SONANG (PREMISE LAW JURNAL, 2017)
ABSTRACT Research on the Implementation of Adjustment Articles of Association of Higher Education based on Government Regulation No. 2 of 2013 , aims to determine how the implementation of the adjustment of the Articles of Association of Higher Education Foundation and to know how the legal consequences of Higher Education Foundation His foundation Statutes adjustment in terms of Government Regulation No. 2 of 2013 .  Implementation of the Regulation is expected to provide legal certainty to the establishment and legal status of higher education foundations , and also became controversial for the foundation in running their business , so it does not deviate from the intent and purpose of its establishment . Inconnection with the proposed research in terms of the approach used in sociological termsis juridical . Data collection techniques in the field of research is associated with the rulesof law which is equipped with library research . Direct communication with the techniques used in the form of unstructured interview guides ( Unstructured interviews ) . Data analysis was done qualitatively and  presented descriptively . Based on the research conducted it could be concluded that , on the theory of legal entities , the foundation said asa legal entity if it has been approved by the Minister . It is also stated in Article 71 of Law Foundation , a foundation that does not make adjustments to the base budget to the limit specified time then can not use the word " foundation " in front of his name .